Photocatalytic property of colloidal TiO2 nanoparticles prepared by sparking process - W. Thongsuwan (2018)
Titanium oxide nanoparticles (NPs) were successfully prepared by sparking off two titanium tips into water for 1-5 h. The nanoparticle-dispersed water was obtained for further characterization. The transmission electron microscopy result shows that the particle size is in the range of 1-5 nm. The electron diffraction patterns and Raman spectra reveal that the as-prepared and the annealed samples at 250 °C are the anatase phase. However, the anatase-rutile phase transformation was observed from the samples at annealing temperature as low as 500 °C. The result of methylene blue-decoloration testing under sunbath suggests that the NPs have good photocatalytic property. © 2007 Elsevier B.V. All rights reserved.